Comparative efficacy of ivermectin (Vermic®), neem and trichlorfon (Negotox®) against humpsore in cattle - Talukder, Milton; Sikder, Subrata; Sarker, Konica; Paul, Ashit Kumar; Amin, Mohammad Rohul (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The experiment was conducted to evaluate the comparative efficacy of ivermectin, neem and trichlorfon against humpsore in cattle. A total of 2765 cattle from different villages of Barisal and Patuakhali district were selected for the diagnosis of humpsore. The prevalence of humpsore was found to be 7.52% in the southern part of Bangladesh. Out of humpsore infected cattle, twenty five (25) cattle between 2 - 7 years of age and irrespective of sexes having typical lesion on hump and neck were selected for the experiment divided into five equals groups (A, B, C, D and E) and each group consists of 05 cattle. Group A kept as control group. Group B was treated with ivermectin (Vermic® @200 ug/kg body weight subcutaneously on 1th and 14th day), group C with neem ointment (20%) topically twice daily for 25 days and group D with trichlorfon 10% (Negotox®) topically twice daily for 25 days and group E was treated with combined ointment (Neem + Trichlorfon 10%) topically twice daily for 25 days. On the basis of the reduction of sore lesions of cattle in all treated groups, the efficacy of ivermectin, neem, trichlorfon and combined ointment (Neem + Trichlorfon 10%) were found 100%, 57.78%, 64.16% and 82.07% at 28 days of post treatment respectively. The present findings demonstrated that ivermectin was much more effective than others therapeutic trials against humpsore in cattle. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 68-74